Neue Banken- und Fiskalarchitektur für Europa: Krisen vermeiden, statt sie nur zu bewältigen - Marcel Fratzscher; Claudia Lambert; Malte Rieth (Wirtschaftsdienst, 2014)
– In December 2013 agreement on the second pillar of the banking union was reached. The SRM sets up restructuring guidelines for banks, including a bank-paid resolution fund, fully operational in 2025. In the article we discuss how the current design of the banking union falls short of the goal of breaking the link between governments and their banks. We explain how an insolvency code for sovereigns is central to achieving this goal and evaluate alternative mechanisms to synchronise the business cycles of member states: 1) the coordination of national stabilisation policies; 2) the introduction of a cyclical shock insurance; and 3) the enlargement of the euro area budget, of which we consider the first alternative the most promising.
Keywords: G15; G28; E32; F36; 330; Bankenkrise; Bankenregulierung; Konjunkturzusammenhang; EU-Staaten